Investigating Levels of Citizenship Values among EFL Students: The Case of Third Year Students at M’sila University - Badis AMROUNE, Mohamed BAALI (UNIVERSITY OF MOHAMED BOUDIAF, 2021)
Citizenship values are of interest especially in the 21st century. This research is about investigating citizenship values among EFL students at M‟sila University; it also aims to explore if learning English has an impact on citizenship values. The used method is the explanatory mixed method, using both qualitative and quantitative tools, i.e. Citizenship Values Levels Scale to measure levels of citizenship values among EFL students, and an Online Questionnaire to explore the influence of learning English on learners‟ citizenship values. Also, an interview is used to shed light on EFL teachers‟ opinions at M‟sila University about levels of citizenship values. The study revealed that EFL learners have good levels at belongingness, loyalty, rights, duties and democracy but average levels at social and political participation. The study findings also reveal that leaning English influences EFL students‟ CVs positively.
Keywords: Keywords: Citizenship values, Learning English as Second Language, EFL Students.